The Influence of Theme-Based Language Teaching toward Indonesian Students’ Reading Comprehension - Ari Safar Wadi; Hizbul Wathoni; Ab. Aziz Bin Sulaiman (International Journal of English and Applied Linguistics (IJEAL), 2021)
Reading is one of the essential skills in English language learning. In the Indonesian context, reading has been one of the essential subjects to be taught among schools and universities since English is one of the compulsory requirements for graduation. Theme-based Language Teaching (TBLT) is a prominent approach used by the teacher and the students to understand the reading. This study aimed at examining the influence of TBLT on the students' reading comprehension. This research used quantitative research with an experimental study. The study selected participants from Madrasah Aliyah (MA) NW Narmada, Indonesia. The study recruited 20 students taken from the second grade of MA NW Narmada. Pre- and post-proficiency tests were used to assemble data of the study. To analyze data, this study employed a T-test to determine the significant result. The result indicated that the pretest score achieved 71.12 and the posttest value reached 89.05. It performed that different values occur on the students' reading comprehension after the TBLT implementation. The significant value (p) also indicated that the output reaches 0.00 < 0.05, which represented the result is under the significant level (0.05). It means that there is a significant influence of the TBLT method on the students' reading comprehension. In other words, TBLT method contributes positive in+uence on the students' English reading comprehension.